Cultural Integration Strategy in Cross-Border Mergers and Acquisitions: A Case Study on Haier Aqau Corporation - Wang, Yemin (Transactions on Economics, Business and Management Research, 2024)
This paper analyzes a cross-border acquisition case in the home appliance industry, Haier AQAU Corporation, which took place between Japanese and Chinese enterprises from 2002 to 2012. This study aims to investigate the strategies that can facilitate the integration of two distinct cultures, China and Japan, following a cross-border acquisition. This research specifically examines the cultural integration strategies used by the acquirer in a successful cross-border merger to effectively reserve and blend the core resources of two companies, utilizing publicly available interviews and information from company websites. The study highlights three crucial elements that cultural integration fostered: the efficiency of enterprise integration, the effectiveness of the promotion system, and the overall performance. Furthermore, this paper offers suggestions for establishing a flexible organizational structure, enhancing employee satisfaction, and creating a compensation system that closely aligns with organizational culture. Future cultural integration approaches to cross-border acquisition between China and Japan could potentially utilize this article to promote maximum win-win for both sides.